Citizen police academies: an analysis of enhanced police-community relations among citizen attendees - Breen, Michael; Johnson, Brian R. (2007)
One current initiated used by many police agencies across the United States to foster better police-community relations is the Citizen's Police Academy(CPA). While CPAs lack a precise academic definition, they can be considered to be a planned programme created by law enforcement agencies to educate their citizens on police operations and management. Over the last 20 years, CPA programmes have rapidly expanded among police agencies in the United States., where it is estimated that approximately 15% of all police agencies have some type of these programmes. This article expands upon the limited research on CPAs by analysing their impact on attendees. Specifically, this article explores changes in the attitudes of 48 CPA attendees who completed a 12 week/36 hour CPA programme at a Sheriff's Department in the state of Michigan. Based on the analysis of pre- and post-test responses, this study found that this particular CPA had a positive impact on the attendees' attitudes toward the police, and their understanding of police operations, crime, and quality-of-life issues in their community. - Reproduced.
Keywords: Police